Dekomposisi Spatial Ketenagakerjaan Sektoral: KABUPATEN DAN KOTA DI PROVINSI RIAU 2001-2006 - Mardiana '; Susi Lenggogeni; Yusni Maulida (Jurnal Ekonomi, 2009)
This paper analyzes spatial structural change, sectoral shift transformation, industrialmix and competitive of employment of in districts and city in Riau. Thus study useddata employment from statistical of people welfare 2001 - 2006. Regional economicstructure can be show held by decomposition method or shift share analysis. Theshare of agriculture sector in total employment has declined steadily, except forRokan Hulu and Rokan Hilir District. Meanwhile the sector of manufactureemployment has trend upward in Indragiri Hilir. The share of trade, hotel andrestaurant sector employment in each district has tendency rising too, except forPelalawan, Rokan Hulu, Rokan Hilir, Pekanbaru and I>umai. Sectoral shift ofagriculture sector highest perform in Indragiri Hilir, mining sector in Bengkalis,manufacture sector in Siak, electrical, water, transportation and communication inDimiai, trade, hotel, restaurant, financial and others services sector in Pekanbaru.Every district in Riau has total share of employment are negative. Meanwhile inDumai, employment raise higher than province, but local factor is unfavorable.Employment in Pekanbaru increasing faster than province with industrialcomposition and local factor was advantage.